State Procurement and Purchase of Livestock Products in Ural Region (1946–1950) - V. N. Mamyachenkov; V. P. Motrevich (Научный диалог)
This article examines the dynamics of state procurement and purchase of livestock products in the Ural region during the first post-war five-year period. The authors utilized materials from two leading federal archives — the State Archive of the Russian Federation and the Russian State Archive of Economy. The study emphasizes the extremity of the examined temporal period. It is demonstrated that even by 1950, the pre-war levels of procurement and purchases of meat, eggs, and wool in the republics and regions of the Ural had not been achieved. The authors conclude that despite annual increases in production, Ural regions only occasionally met the established procurement targets, as these targets were generally set unrealistically high. It is underscored that the system of state procurement and purchase of agricultural products effectively functioned as a form of natural taxation. Furthermore, it is asserted that by 1950, livestock farming in the Ural region remained in a dire state, as evidenced by the dynamics of state procurement and purchases during the first post-war five-year period. The conclusion drawn is that during extreme periods in the history of Russia and the USSR, this system convincingly demonstrated its urgent necessity.